From Quality to Loyalty: How Product Excellence and Effective Promotion Drive Customer Commitment - Fadillah, Yusuf Rachmat; Paramitra, Yuaniko; Razak, Ismail; Rahmawantar, Dhistianti Mei (Research of Business and Management, 2024)
The purpose of this study was to determine the influence of product quality and promotion on customer loyalty. The study was conducted on Shopee customers in Rawamangun, East Jakarta. The population used in this survey are Shopee customers in Rawamangun, East Jakarta. The method of sample selection in this study was using an incidental sampling technique. The results of the study showed that, in part, the quality of the product has a positive and significant effect on customer loyalty. The product quality regression coefficient was positively marked as 0.464, and the promotion had a positive and significant effect on customer loyalty. The coefficient of regression of the positively marked promotion is 0.535. Implications Management needs to constantly invest resources in research and development (R&D) to ensure that the products produced always meet or even exceed customer expectations. Superior product quality and effective promotion can increase brand equity and differentiate the company from competitors. By understanding and applying these implications, managers can make better decisions in designing products and marketing campaigns aimed at increasing customer loyalty, which ultimately contributes to the long-term growth of the business.